2018
DOI: 10.21037/atm.2018.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical emboli following a pulmonary embolus in the presence of a patent foramen ovale

Abstract: A paradoxical embolism is defined as a systemic arterial embolus due to passage of a venous thrombus through a right to left shunt. We describe a case of acute cerebral vascular accident (CVA), right subclavian arterial embolus, and pulmonary emboli in the setting of a large patent foramen ovale (PFO). A 74-year-old woman with multiple comorbidities presented to the emergency department with acute onset of shortness of breath, weakness, and right arm pain. She was found to have bilateral pulmonary emboli, left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
3
1
1
Order By: Relevance
“…At the same time it is worth considering that not all PFOs are of the same size. Smaller PFOs have less blood flow and therefore a lower chance of a thrombus crossing [26,27]. Interestingly, we found an even higher frequency of association of stroke in our group of patients with PFOwoPE (39.2%), but the difference was not statistically significant (P = 0.682).…”
Section: Discussioncontrasting
confidence: 59%
“…At the same time it is worth considering that not all PFOs are of the same size. Smaller PFOs have less blood flow and therefore a lower chance of a thrombus crossing [26,27]. Interestingly, we found an even higher frequency of association of stroke in our group of patients with PFOwoPE (39.2%), but the difference was not statistically significant (P = 0.682).…”
Section: Discussioncontrasting
confidence: 59%
“…1d). Paradoxical renal thromboembolic events – although rare – are already reported in literature, 2,3 while PFO is a well known cardiac source of embolism, especially in case of right atrial pressure increase 4,5 . In our case, the clinical picture suggested that an abrupt increase in PAPs due to paraneoplastic pulmonary embolism created a paradoxical embolization in the kidneys through an otherwise silent PFO.…”
mentioning
confidence: 48%
“…Paradoxical renal thromboembolic events -although rare -are already reported in literature, 2,3 while PFO is a well known cardiac source of embolism, especially in case of right atrial pressure increase. 4,5 In our case, the clinical picture suggested that an abrupt increase in PAPs due to paraneoplastic pulmonary embolism created a paradoxical embolization in the kidneys through an otherwise silent PFO. Patient was successfully treated with subcutaneous heparin in the acute phase and with long-term anticoagulants (Apixaban 10 mg twice daily for 7 days followed by 5 mg twice daily).…”
Section: Images In Cardiovascular Medicinementioning
confidence: 60%
“…Так, например, у пациентов, гетерозиготных по полиморфизмам фактора V свертывания крови (мутация Лейдена) или мутациям гена PROC, изменение статуса от повышенного свертывания до венозного тромбоза запускается взаимодействием генетических и средовых факторов. Примером негенетических факторов может быть наличие беременности, прием пероральных противозачаточных средств, пожилой возраст, обездвиживание, новообразования, патология сердца, постоперационное состояние [34][35][36][37].…”
Section: геномика и протеомика как новые перспективные методы диагносunclassified